Segmentasi Warna Kulit Menggunakan Ruang Warna YCBCR Untuk Deteksi Wajah Manusia - Yovi Apridiansyah; erwin dwika putra; Diana Diana; Angtyas Candra Pratama (Jurnal Media Infotama, 2023)
Image processing is a system where the process is done by entering in the form of imagery and the result is also in the form of imagery. At first this image processing was done to improve the quality of the image, but with the development of the world of computing which is characterized by increasing the capacity and speed of computer processes. In this research image processing will be used for skin color detection which is the initial process in image processing. Success in detecting pixel imagery can be a category of skin or not skin seen from the results of processing processes such as the process of detecting human faces. Skin detection is also a process of finding skin pixels of color in the area of the image or video, this process is usually used as a preprocessing step to find areas that could potentially have a human face. In this study by applying the color space YcbCr we were able to detect faces in humans with a high percentage accuracy rate with a precession percentage of 77%, Recal 87% and an accuracy rate of 72% from the results of 10 image samples.